Implementation of Internet of Things (IoT) in Education: A Systematic Literature Review - Prasetya, Luhur Adi; Rofiudin, Amir; Herwanto, Heru Wahyu (Journal of Education and Computer Applications, 2025)
This study aims to analyze the development, benefits, and challenges of implementing the Internet of Things (IoT) in education through a systematic literature review (SLR). Using the PRISMA method, 25 relevant articles published between 2018 and 2025 were selected from leading academic databases, including Scopus, IEEE Xplore, SpringerLink, and ScienceDirect. The review process involved four stages: identification, screening, eligibility, and inclusion. The findings show that IoT significantly improves learning effectiveness, increasing outcomes by up to 30% through smart classrooms, real-time monitoring, automated attendance systems, and personalized learning. In addition, IoT supports operational efficiency in schools, with reports showing energy consumption savings of up to 25% and better security measures. Despite these benefits, challenges such as infrastructure gaps (especially in rural areas, which were recorded in 40% of the studies), data privacy issues, and limited digital readiness among teachers remain. This study is limited to English-language publications from 2018-2025. Its originality lies in offering an integrative analysis that connects technological and pedagogical perspectives, providing strategic insights for inclusive and sustainable digital education.